Preparation, Physicochemical Characterization and Anti-Fungal Evaluation of Amphotericin B-Loaded PLGA-PEG-Galactosamine Nanoparticles - Ghobad Mohammadi; Mostafa Fathian-Kolahkaj; Pardis Mohammadi; Khosro Adibkia; Ali Fattahi (Tabriz University of Medical Sciences, 2021)
Purpose: The present study aimed to formulate PLGA and PLGA-PEG-galactosamine nanoparticles (NPs) loaded with amphotericin B with appropriate physicochemical properties and antifungal activity. PLGA was functionalized with GalN to increase the adhesion and antifungal activity of NPs against Candida albicans. Methods: The physicochemical properties of NPs were characterized by particle size determination, zeta potential, drug crystallinity, loading efficiency, dissolution studies, differential scanning calorimeter (DSC), X-ray powder diffraction (XRPD), and Fourier transform infrared (FT-IR). Antifungal activity of the NPs at different drug/polymer ratios was examined by determining minimum inhibitory concentrations (MICs). Results: the FT-IR and 1 HNMR analysis successfully confirmed the formation of PLGA- PEG-GalN NPs. The PLGA NPs were in the size range of 174.1 ± 3.49 to 238.2±7.59 nm while PLGA-GalN NPs were 255.6 ±4.08 nm in size, respectively. Loading efficiency was in the range of 67%±2.4 to 77%±1.6, and entrapment efficiency in the range of 68.185%±1.9 to 73.05%±0.6. Zeta potential and loading efficiency for PLGA-GalN NPs were -0.456, 71%. The NPs indicated an amorphous status according to XRPD patterns and DSC thermograms. The PLGA-PEG-GalN NPs showed higher fungistatic activity than PLGA NPs. Conclusion: the results demonstrated that the antifungal activity of PLGA-PEG-GalN NPs was higher than pure amphotericin B and PLGA NPs.